2020
DOI: 10.3892/br.2020.1337
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑obesity effect of Carica papaya in high‑fat diet fed rats

Abstract: The present study evaluated the anti-obesity properties of papaya in high-fat (HF) diet fed rats. In the in vitro portion of the present study, the effects of papaya juice on pancreatic lipase enzyme activity was assessed, and it was shown that papaya exhibited an inhibitory effect on these enzymes. In the in vivo portion of the study, papaya was found to reduce the expression levels of markers of obesity, inflammation and oxidative stress in rats. Obesity was induced in 28 male Sprague Dawley rats by feeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…30 A long-term high-fat diet could lead to disorders of the body's lipid metabolism, liver lipid accumulation and hyperglycemic status in rats, 33 intensifying glucose oxidation to produce excessive oxidative products. Chronic intake of highfat diet has been proved to increase the prevalence of LMD and relative diseases, 34 such as obesity, hyperlipidemia, insulin resistance and cardiovascular disease. In this study, after 8 weeks of high-fat diet feeding, the level of blood lipids increased significantly, accompanied by reduced insulin sensitivity and imbalance of glucose homeostasis.…”
Section: Food and Function Papermentioning
confidence: 99%
“…30 A long-term high-fat diet could lead to disorders of the body's lipid metabolism, liver lipid accumulation and hyperglycemic status in rats, 33 intensifying glucose oxidation to produce excessive oxidative products. Chronic intake of highfat diet has been proved to increase the prevalence of LMD and relative diseases, 34 such as obesity, hyperlipidemia, insulin resistance and cardiovascular disease. In this study, after 8 weeks of high-fat diet feeding, the level of blood lipids increased significantly, accompanied by reduced insulin sensitivity and imbalance of glucose homeostasis.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Somanah and co-workers revealed that papaya extracts at a dose of 2 mg/mL showed protective effects through attenuated ROS production and pro-inflammatory cytokines secretion of interleukin-6 (IL-6) and TNF-α as well as upregulating antioxidant enzymes activities [ 18 ]. Another in vivo study showed that papaya juice demonstrated anti-obesity properties by reducing obesity markers, inflammation and oxidative stress in high-fat diet rats by upregulating SOD levels, attenuated serum malondialdehyde (MDA), PPAR-γ, lipid peroxidation, and ROS production at a treatment dose of 1 mL per 100 g of body weight [ 19 ].…”
Section: Carica Papaya Counteracts Oxidative Stress In Inflammation Skin Aging and Healing Chronic Diseases And Cancersmentioning
confidence: 99%
“…In addition, a range of phytochemicals with great strength of anti-inflammatory effect, such as benzyl isothiocyanate (BiTC), β-carotene, lycopene, and vitamin C could be found in various parts of papaya fruits, in either pulp or seeds. These phytochemicals were proven to inhibit pro-inflammatory cytokines including TNF-α, IL-6 and monocyte chemoattractant protein-1 (MCP-1) [ 18 , 19 ]. In addition, polyphenols within Carica papaya could act as free radical scavenger and at the same time exerting its effects in upregulating the antioxidant enzymes activities [ 18 ].…”
Section: Carica Papaya Counteracts Oxidative Stress In Inflammation Skin Aging and Healing Chronic Diseases And Cancersmentioning
confidence: 99%
“…Chronic consumption of a high fat diet has been shown to increase adipogenesis. Fats are transported to the blood system and delivered to the adipose tissue and liver, leading to lipid accumulation and the development of adipogenesis [ 54 , 55 ]. In this study, adipogenesis in SW-872 was induced by oleic acid treatment, which is actually a potent adipogenic promoter.…”
Section: Discussionmentioning
confidence: 99%